Science and subjectivity from Hilton's perspective Japiassu - Oliveira, Vanessa Sousa de (Universidade Estadual de Campinas, 2019)
The epistemological transformations that we have witnessed within the past fifty years, grounded on the questioning to Positivism, have profoundly changed the way of thinking the relationship between science and subjectivity. In this context, it is appropriate to ask about how this relationship is addressed in the Human/Social Sciences. The essay discourses about how the Epistemologies of Subjectivity are presented before this relationship, what is the social role delegated to the scientist, subject and object of his or her ownpractices, and how the discussion is covered by the philosopher Hilton Japiassu.